BACILLARY LAYER DETACHMENT: MULTIMODAL IMAGING AND HISTOLOGIC EVIDENCE OF A NOVEL OPTICAL COHERENCE TOMOGRAPHY TERMINOLOGY. Issue 11 (November 2021) - Ramtohul, Prithvi; Engelbert, Michael; Malclès, Ariane; Gigon, Edward; Miserocchi, Elisabetta; Modorati, Giulio; Cunha de Souza, Eduardo; Besirli, Cagri G.; Curcio, Christine A.; Freund, K. Bailey
Abstract : Purpose: To clarify the histologic basis of bacillary layer detachment (BALAD) through a review of the current literature and an analysis of retinal imaging. Methods: The literature for previous reports of BALAD were reviewed. An analysis of retinal images was performed to support anatomical conclusions. Results: A total of 164 unique patients with BALAD on optical coherence tomography (OCT) were identified from the published literature. Twenty-two underlying etiologies, all associated with subretinal exudation, were identified. Forty-one different OCT terminologies were found. The defining OCT feature of BALAD was a split at the level of the photoreceptor inner segment myoid creating a distinctive intraretinal cavity. Resolution of BALAD was followed by a rapid restoration of the ellipsoid zone. Histology of age-related macular degeneration eyes suggests that individual photoreceptors can shed inner segments. Furthermore, detachment of the entire layer of inner segments is a common postmortem artifact. It is proposed that BALAD occurs when outwardly directed forces promoting attachment of photoreceptor outer segments to the retinal pigment epithelium exceed the tensile strength of the photoreceptor inner segment myoid. Conclusion: This review serves to strengthen the OCT nomenclature "bacillary layer detachment, " based on specific reflectance information obtained by OCT and previously published histologic observations. Abstract : Supplemental Digital Content is Available in the Text. The "bacillary layer detachment" describes a detachment of the photoreceptor inner and outer segments resulting from a split within the inner segment myoids. Using a literature review, we explored associated diagnoses and resolved inconsistent descriptions for the anatomical basis of this finding through correlation with histologic data and retinal imaging.